Budaya Dan Lingkungan Industri Media Islam - Moch Nurcholis Majid (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2022)
Every company has its own corporate culture, in this case to implement company values ​​or activities that can make it a habit for employees to always be tied to the company's system. In essence, every company uses a work culture that makes employees comfortable at work. Every company uses a work culture that makes employees comfortable at work. With a culture and a comfortable work environment for employees so that it is easy to achieve a goal of the vision and mission of a company